The Relationship Between Mother's Knowledge And Exclusive Breast Feeding In The Work Area Of Bingai Public Health Center, Wampu District Langkat Regency - Martaulina Sinaga; Nur Afiqah Mohamad; Siti Nurmawan Sinaga; Lidya Natalia Sinuhaji; Risna Yasina Manik; Hepriani Girsang (Sean Institute, 2021)
Mother's Milk (ASI) is the first, main and best food at the beginning of a baby's natural life. According to the Global Strategy on Infant and Young Child Feeding, proper feeding is breastfeeding the baby as soon as possible after birth, exclusive breastfeeding until the age of 6 months, providing proper and adequate complementary food for breastfeeding from the age of 6 months, and continuing breastfeeding until the age of 2. years or more. Exclusive breastfeeding until the baby is 6 months old is very beneficial because it can protect the baby from various diseases that cause infant death. In addition to benefiting the baby, exclusive breastfeeding also benefits the mother, namely reducing postpartum bleeding, reducing blood loss during menstruation, accelerating weight gain, reducing the risk of breast cancer and uterine cancer (Widodo, 2011). According to Lawrence Green (1980) in Notoadmodjo (2015) there are various factors that influence exclusive breastfeeding including mother's knowledge about exclusive breastfeeding, education, psychology, infant abnormalities, breast abnormalities, availability of resources/facilities, affordability of facilities, attitudes and behavior of health workers .